WEBVTT
00:00:00.720 --> 00:00:13.520
Find π΄ minus π΅, given π΄ is equal to five π₯ cubed minus three π₯ and π΅ is equal to negative six π₯ squared plus three π₯.
00:00:14.400 --> 00:00:23.800
In order to answer this question, we need to subtract negative six π₯ squared plus three π₯ from five π₯ cubed minus three π₯.
00:00:24.520 --> 00:00:33.200
Before we start, itβs important to remember that we can only collect or group terms with the same exponent or power.
00:00:33.760 --> 00:00:43.000
In this case, the only terms we can group together are negative three π₯ and positive three π₯.
00:00:44.000 --> 00:00:48.280
We also need to remember our rules when two signs are touching.
00:00:48.920 --> 00:00:57.000
If we have two positive signs, the resultant sign is a positive one or an addition sign.
00:00:57.720 --> 00:01:09.040
When we have a positive and a negative sign, in either order, our resultant sign is a negative or subtraction sign.
00:01:09.560 --> 00:01:18.320
And when we have two negative signs, the resultant sign is positive or addition.
00:01:18.920 --> 00:01:24.840
The only term with π₯ cubed in it is the first one, five π₯ cubed.
00:01:25.400 --> 00:01:29.040
So this too must be in our answer.
00:01:29.520 --> 00:01:32.880
We have a negative six π₯ squared term.
00:01:33.200 --> 00:01:35.120
However, this term is being subtracted.
00:01:35.440 --> 00:01:40.120
In other words, we have negative negative six π₯ squared.
00:01:40.640 --> 00:01:44.240
Two negatives become a positive.
00:01:44.800 --> 00:01:51.000
Therefore, this is the same as six π₯ squared or positive six π₯ squared.
00:01:51.840 --> 00:01:59.200
Finally, we need to group the π₯ terms, negative three π₯ minus positive three π₯.
00:01:59.680 --> 00:02:05.040
This time, our sign will become a subtraction or negative sign.
00:02:05.640 --> 00:02:11.560
So weβre left with negative three π₯ minus three π₯.
00:02:12.240 --> 00:02:16.720
Negative three minus three is equal to negative six.
00:02:17.480 --> 00:02:24.040
Therefore, negative three π₯ minus three π₯ equals negative six π₯.
00:02:24.760 --> 00:02:45.400
This means that if π΄ is equal to five π₯ cubed minus three π₯ and π΅ is equal to negative six π₯ squared plus three π₯, then π΄ minus π΅ equals five π₯ cubed plus six π₯ squared minus six π₯.